Effects of preferential tax treatment on German homeownership - Stefanie Braun (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
The paper analyzes the effects of mortgage interest deductibility and untaxed imputed rental income on the German homeownership. I use a general equilibrium life-cycle framework, where a minimum down-payment constraint on purchases of housing capital is the critical element of the model framework. I find that both tax policies would increase Germany's low homeownership rate. However, these tax policies would entail substantial welfare losses for individuals of all income quintiles in the long run. Finally, wealth effects are relatively small and the welfare analysis shows that individuals would prefer to live in an economy without preferential tax treatment of housing.
Keywords: E62; H3; 330; German homeownership rate; Housing taxation; Imputed rents; Mortgage deductibility; Capital accumulation